Endophthalmitis caused by Bacteroides fragilis after pars plana vitrectomy and treatment approach - Yildirim, Hakan; Balbaba, Mehmet; Yilmaz, Turgut; Toraman, Zulal Asci (Wolters Kluwer Medknow Publications, 2022)
Rationale: Endophthalmitis is an uncommon but serious ocular infection often resulting in probable visual loss. Bacteroides fragilis is a rare cause of endophthalmitis. Patient concerns: A 46-year-old male patient complained of eye pain and low vision after pars plana vitrectomy. Diagnosis: Bacteroides fragilis endophthalmitis after pars plana vitrectomy was diagnosed. Interventions: Pars plana vitrectomy and silicone oil implantation were performed. Outcomes: Early treatment and choice of tamponade in endophthalmitis after pars plana vitrectomy may possibly prevent evisceration and progression of endophthalmitis. Lessons: Bacteroides fragilis can be seen in cases of endophthalmitis after pars plana vitrectomy.
Keywords: Bacteroides fragilis; Endophthalmitis; Pars plana vitrectomy